2013
DOI: 10.1523/jneurosci.5084-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neural Evidence for Individual and Cultural Variability in the Social Comparison Effect

Abstract: Although several studies have investigated the neural mechanism of social comparison, it remains unclear whether and how cultural membership, particularly independent versus interdependent cultures, may differentially shape the neural processes underlying social comparison. In the present functional magnetic resonance imaging (fMRI) study, we examined the behaviors and neural response patterns of Korean (i.e., interdependent culture) and American (i.e., independent culture) participants while performing a fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 49 publications
6
36
1
Order By: Relevance
“…The neural responses to the reward outcomes were analyzed based on a three-factor model that sep-arated the effects of the outcome for SELF, that for OTHER, and equality in the outcomes between the players (see Materials and Methods). As expected, both the VS and vmPFC were sensitive to the reward outcome for SELF (Table 1), consistent with the large literature describing the role of these regions in processing monetary reward outcomes (Tricomi et al, 2004;Fliessbach et al, 2007;Mobbs et al, 2009;Haber and Knutson, 2010;Kang et al, 2013). Furthermore, the vmPFC showed an increased activation to the equality in the outcomes between the players (Table 1), in line with the results of previous studies reporting vmPFC activations to equitable monetary allocations between self and other (Tabibnia et al, 2008;Tricomi et al, 2010;Baumgartner et al, 2011;Zaki and Mitchell, 2011).…”
Section: Neural Response To Reward Outcomesupporting
confidence: 85%
See 1 more Smart Citation
“…The neural responses to the reward outcomes were analyzed based on a three-factor model that sep-arated the effects of the outcome for SELF, that for OTHER, and equality in the outcomes between the players (see Materials and Methods). As expected, both the VS and vmPFC were sensitive to the reward outcome for SELF (Table 1), consistent with the large literature describing the role of these regions in processing monetary reward outcomes (Tricomi et al, 2004;Fliessbach et al, 2007;Mobbs et al, 2009;Haber and Knutson, 2010;Kang et al, 2013). Furthermore, the vmPFC showed an increased activation to the equality in the outcomes between the players (Table 1), in line with the results of previous studies reporting vmPFC activations to equitable monetary allocations between self and other (Tabibnia et al, 2008;Tricomi et al, 2010;Baumgartner et al, 2011;Zaki and Mitchell, 2011).…”
Section: Neural Response To Reward Outcomesupporting
confidence: 85%
“…Together, the vmPFC seems to play a more important role than the VS in valuation of social information including equality in opportunity. Meanwhile, some other studies have reported that the vmPFC and VS show similar responses to social contexts (Tricomi et al, 2010;Bault et al, 2011;Kang et al, 2013). Future research will benefit from clarifying whether and how the vmPFC and VS are differentially involved in reward processing within a range of social contexts.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study we did not observe, however, activations in the ventral striatum (VS) for downward comparisons, although such activations have been reported on several occasions before (Bault et al, 2011;Dohmen, Falk, Fliessbach, Sunde, & Weber, 2011;Du et al, 2013;Dvash, Gilam, Ben-Ze'ev, Hendler, & Shamay-Tsoory, 2010;Fliessbach et al, 2007Fliessbach et al, , 2012Grygolec, Coricelli, & Rustichini, 2012;Kang, Lee, Choi, & Kim, 2013;Lindner et al, 2015; for a review see . The VS constitutes one of the main structures of the reward system.…”
Section: Discussioncontrasting
confidence: 67%
“…(B) The vmPFC tracks the level of equality of opportunity between self and other, whereas the ventral striatum tracks the amount of opportunities available to self. design cultural neuroscience research (Chiao, 2010;Kang et al, 2013).…”
Section: Equality Of Outcome Vs Equality Of Opportunity: Possible DImentioning
confidence: 99%